Uptake, Outcomes, and Costs of Implementing Non-invasive Prenatal Testing for Down Syndrome Into NHS Maternity Care: Prospective Cohort Study in Eight Diverse Maternity Units. Issue 11 (November 2016) - Chitty, Lyn S.; Wright, David; Hill, Melissa; Verhoef, Talitha I.; Daley, Rebecca; Lewis, Celine; Mason, Sarah; McKay, Fiona; Jenkins, Lucy; Howarth, Abigail; Cameron, Louise; McEwan, Alec; et al.
Abstract : (Abstracted from BMJ 2016;354:i3426) Noninvasive prenatal testing, also known as cell-free DNA (cfDNA) screening, is an efficient screening test for Down syndrome with roughly 99% sensitivity and false-positive rates of less than 0.1% in both high-risk and general populations. This study aimed to examine the potential costs and consequences of introducing cfDNA screening in the public sector Down syndrome screening pathway as an additional screening test dependent on the risk generated by current screening.